Akhlak Guru Perspektif Syekh Abdul Wahab Al-Sya’rani dalam Kitab Al-Minah Al-Saniyah - Mochammad Shofwan Hidayatulloh; Fatkur Rohman; Tatik Wijayanti; Moh. Ismail (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
, , And In the world of education today, society is often criticized due to cases of teacher behavior that show disgraceful attitudes. Some teachers are involved in sexual harassment of their own students, criminal acts, etc. This action has disturbed the community, especially parents. So it is important that teacher morals are the first and basic thing that teachers must have.The problems studied are 1) what is the teacher's morals from the perspective of Sheikh Abdul Wahhab al-Sya'rani in the book al-Minah al-Saniyah?, 2) what is the relevance of the teacher's morals from the perspective of Sheikh Abdul Wahhab al-Sya'rani in Islamic Religious Education? In answering this problem, the researcher analyzed qualitative research using a library model. By using data collection techniques in the form of documentaries.The results of the research can be concluded that: 1) Sheikh Abdul Wahab al-Sya'rani expressed his views regarding teacher morals in the book al-Minah al-Saniyah, there are two important points, namely the division of teacher morals based on their dimensions and the division of teacher morals based on their objects. The division of teacher morals based on dimensions is: Teacher Morals, Tahzib Dimension; repent and increase istighfar. Tafakkur Dimension Teacher Morals; Uzlah (seclude yourself and be silent) and dhikr. Teacher's Moral Dimension of Charity; Praying at night and praying in congregation, Doing good things to others, Not tyrannizing (hurting) others, Avoiding haram things, Having a sense of shame, Being honest in your work, Abandoning permissible things, Avoiding riya' behavior and Fighting lust. The division of teacher morals based on the object is: Morals towards Allah SWT; repentance, dhikr, istighfar, congregational prayer and night prayer. Morals towards others (humans); do good to others, do not wrong others, do not show off (riya'). Moral towards oneself; avoiding unlawful things, having a sense of shame, being honest in work, isolating oneself and being silent, abandoning permissible things and fighting lust. 2) The morals of teacher Abdul Wahab al-Sya'rani's perspective in everyday life are currently considered very relevant. This is proven by the various problems that befell the nation's generation, it is very necessary to provide maximum education and moral development for teachers so that they can prevent undesirable things from happening, and at least eliminate the problems that have occurred. Thus, it can be concluded that Abdul Wahab al-Sya'rani's thoughts about teacher morals are very relevant in Islamic religious education and in everyday life.